2008
DOI: 10.3851/imp1295
|View full text |Cite
|
Sign up to set email alerts
|

α-Galactosylceramide in Chronic Hepatitis B Infection: Results from a Randomized Placebo-Controlled Phase I/ II Trial

Abstract: alpha-GalCer (0.1-10 microg/kg) used as monotherapy for chronic hepatitis B infection resulted in a strong decrease of NKTs, but did not clearly affect HBV DNA and alanine aminotransferase levels. alpha-GalCer was poorly tolerated and is unlikely to be suitable as an alternative monotherapy to the current treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 31 publications
6
67
0
Order By: Relevance
“…11 Additionally, the clinical trial demonstrated that glycosphingolipid alpha-galactosylceramide could be used as a monotherapy for CHB by the regulation of antiviral immune responses. 12 We previously found that glycosphingolipid and sphingomyelin were closely related to hepatic necroinflammation and steatosis in chronic hepatitis C patients, respectively. 13,14 Recently we also found that serum dihydroceramide may be a useful prognostic indicator for the early prediction of HBV-related acute-on-chronic liver failure.…”
mentioning
confidence: 99%
“…11 Additionally, the clinical trial demonstrated that glycosphingolipid alpha-galactosylceramide could be used as a monotherapy for CHB by the regulation of antiviral immune responses. 12 We previously found that glycosphingolipid and sphingomyelin were closely related to hepatic necroinflammation and steatosis in chronic hepatitis C patients, respectively. 13,14 Recently we also found that serum dihydroceramide may be a useful prognostic indicator for the early prediction of HBV-related acute-on-chronic liver failure.…”
mentioning
confidence: 99%
“…Thus, the subsequent activation of NK/CD8 + T cells owing to IFN‐γ becomes the most powerful forces against HBV replication 13. Even though NK/CD8 T cells will take the place of overactivated iNKT cells, a randomized placebo‐controlled trial still failed to detect the success inhibition of HBV DNA in α‐Galcer‐treated patients with CHB, which we had to attribute this failure to the poor tolerance of α‐Galcer or the obvious drop of iNKT cell number 19. Constantly, we found α‐Galcer largely reduced the percentage of hepatic iNKT cells as well as the cell number in the mice models.…”
Section: Discussionmentioning
confidence: 99%
“…This, together with the availability of new methods and tools to study iNKT cells, has led to renewed interest in their regulatory functions in health as well as their manipulation in various diseases. A synthetic glycolipid compound called α-galactosylceramide (αGC) that binds to CD1d and triggers iNKT cell activation in a TCR-dependent fashion [11] has been used as a model glycolipid agonist of iNKT cells in numerous animal models of human diseases, and also as a potential therapeutic agent in several clinical trials in patients with cancer [12][13][14] and viral infectious diseases [15,16].…”
Section: Introductionmentioning
confidence: 99%